Oil Price and Slumps Effects on Personal Consumption in Saudi Arabia - Mahmood, Haider; Zamil, Ahmad M.A. (International Journal of Energy Economics and Policy, 2019)
Oil price movements and its macroeconomic effect may have deep effects on the oil exporting economy like Saudi Arabia in terms of personal consumption and welfare derived from the consumption. This present research targets to isolate the relationship between oil price and personal consumption per capita using a period 1970-2016 and applying cointegration technique. We find that all variables are the first different stationary and long and short run relationships are also corroborated. We find the positive relationship between oil price and personal consumption per capita in both long and short runs which suggest that oil price has direct effect on the consumption of the Kingdom in case of any movement. Moreover, we find that the oil price crises have insignificant effects on the personal consumption per capita hence the economy's consumption is supported by non-oil sector in the slump periods. Based on findings, we suggest the diversification policy to the Saudi economy for a smooth consumption pattern in the long run. Keywords: Personal consumption per capita, Oil price, Oil price slumps, cointegration. JEL Classifications: E21; Q21; H12 DOI: https://doi.org/10.32479/ijeep.7763